Morphometric characteristics of the repair-mathematic stage of the mechanical fort (salmotruttam. fariol) virtual in the conditions of industrial economics «Ishkhan» - Кучерук, А. І.; Мрук, А. І.; Галоян, Л. Л. (Scientific Progress & Innovations, 2017)
In this paper we analyzed the morphometric parameters of the repair broodstock brook trout (Salmo trutta m. Fario L.) under industrial conditions. Most of the analyzed features were characterized by a relatively low degree of variability – the coefficient of variation ranged from 3.8 to 13.1 %. The fish significantly increased body weight, while the proportions of the body, in general, were characteristic of the brook trout-natural watercourses. In this case, the cultured fish decreased the horizontal diameter of the eye, and the length of the snout increased, which was the result of adaptive changes in the specific conditions of growing in the basins. The carried out investigations showed no negative changes in the exterrug trout.